PERSEPSI WISATAWAN TERHADAP DAYA TARIK WISATA PANTAI AMMANI DI KABUPATEN PINRANG PROVINSI SULAWESI SELATAN - Bibin, Muhammad; Kaswiran, Kaswiran; Wahyudi, Adi (Jurnal Sains dan Teknologi Perikanan, 2022)
Ammani Beach is a beach tourist attraction that has quite a variety of attractions. This beach tourism activity is included in the recreational category, which is the type of activity that is most dominantly carried out by tourists. Ammani Beach tourism seems to be in the involvement phase. The involvement phase is marked by an increase in visitors who encourage local residents to offer facilities exclusively to visitors/tourists. In this phase, there is pressure on the government to provide supporting facilities for tourists. A tourist attraction will develop because of the presence of tourists, without tourists visiting a tourist attraction location, the tourist attraction will be difficult to develop. This study aims to describe tourists' perceptions of objects and natural tourist attractions, infrastructure and facilities in the Ammani Beach area. Sampling in this study was carried out on tourists visiting the Ammani Beach area as many as 30 people using the accidental sampling method. Data collected using questionnaires and analyzed through descriptive analysis. The results showed that the perception of tourists about Ammani Beach is very good in terms of tourism support facilities, the condition of the beach is still natural and clean. Public transportation facilities to the tourist sites of Ammani Beach are still lacking. The local community is very friendly and open to the presence of tourists because their awareness of increasing the economic sector in their area can prosper the community if the beach is crowded with tourists.